Current trends on protein driven bioinks for 3D printing - Veiga, Anabela (2021)
In the last decade, three-dimensional (3D) extrusion bioprinting has been on the top trend for innovative technologies in the field of biomedical engineering. In particular, protein-based bioinks such as collagen, gelatin, silk fibroin, elastic, fibrin and protein complexes based on decellularized extracellular matrix (dECM) are receiving increasing attention. This current interest is the result of protein’s tunable properties, biocompatibility, environmentally friendly nature and possibility to provide cells with the adequate cues, mimicking the extracellular matrix’s function. In this review we describe the most relevant stages of the development of a protein-driven bioink. The most popular formulations, molecular weights and extraction methods are covered. The different crosslinking methods used in protein bioinks, the formulation with other polymeric systems or molecules of interest as well as the bioprinting settings are herein highlighted. The cell embedding procedures, the in vitro, in vivo, in situ studies and final applications are also discussed. Finally, we approach the development and optimization of bioinks from a sequential perspective, discussing the relevance of each parameter during the pre-processing, processing, and post-processing stages of technological development. Through this approach the present review expects to provide, in a sequential manner, helpful methodological guidelines for the development of novel bioinks.